Tagyîr Mawdhî’ Inhirâf Qiblat al-Masjid fî Bamîkasân ‘alâ Asasi al-Tiknôlôjiyya al-Mutaqaddimah: al-Tahlîla al-Ijtimâ’î wa al-Tsaqafî - Hosen; Abdul Jalil; Abd. Wahed; Ach. Muzayyin; Ziyad Ravaşdeh (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
Reposition of wrongly-established qibla direction typically brings into controversy, particularly among takmir as the mosque officiants. However, what occured in Pamekasan shows different trends. This research therefore focuses on how the Pamekasan based takmir responded on the qibla direction reposition issue. It is a descriptive one based on qualitative data. The data was collected using interview to the takmir and participatory observation at the research locus. The obtained data was then sorted and systematically arranged for verification to draw a conclusion. The research comes to a conclusion that; first, the deviation of qibla direction on the research locus was caused by wrongly-determined direction in the initial mosque building process due to the ignorance of Islamic astronomy or so called ilmu falaq theories. The mistake was figured out trough verification on the sun image and qiblat direction application. Second; the reposition was initiated by takmir who firstly consulted with experts on Islamic law and falaq, made scientific investigation by rechecking the mosque qibla direction using advanced technology, then announced the process result to the mosque congregation, and made a deliberation forum before doing the reposition replacing the older with the more accurate and newer one. Third; takmirs’ perception on the mosque qibla reposition tends to be supporting rather than opposing.